Influence of binder type and process parameters on the compression properties and microbial survival in diclofenac tablet formulations - John Oluwasogo Ayorinde; Oludele Adelanwa Itiola; Oluwatoyin Adepeju Odeku; Michael Ayodele Odeniyi (Universidade de São Paulo, 2011)
The influence of binder type and process parameters on the compression properties and microbial survival in diclofenac tablet formulations were studied using a novel gum from Albizia zygia. Tablets were produced from diclofenac formulations containing corn starch, lactose and dicalcium phosphate. Formulations were analyzed using the Heckel and Kawakita plots. Determination of microbial viability in the formulations was done on the compressed tablets of both contaminated and uncontaminated tablets prepared from formulations. Direct compression imparted a higher plasticity on the materials than the wet granulation method. Tablets produced by wet granulation presented with a higher crushing strength than those produced by the direct compression method. Significantly higher microbial survival (p< 0.05) was obtained in formulations prepared by direct compression. The percent survival of Bacillus subtilis spores decreased with increase in binder concentration. The study showed that Albizia gum is capable of imparting higher plasticity on materials and exhibited a higher reduction of microbial contaminant in the formulations. The direct compression method produced tablets of reduced viability of microbial contaminant. A influência do tipo de ligante e os parâmetros do processo de propriedades de compressão e sobrevivência microbiana em comprimidos de diclofenaco foram estudados utilizando uma nova goma de Albizia zygia. Os comprimidos foram produzidos a partir de formulações de diclofenaco contendo amido de milho, lactose e fosfato bicálcico. As formulações foram analisadas usando os gráficos de Heckel e Kawakita. A determinação da viabilidade microbiana nas formulações foi feita nos comprimidos contaminados e não contaminados preparados a partir de formulações. A compressão direta confere maior plasticidade dos materiais do que o método de granulação úmida. Comprimidos produzidos por granulação úmida apresentaram maior força de esmagamento do que aqueles produzidos pelo método de compressão direta. Observou-se sobrevivência significativamente maior (p<0,05) em formulações preparadas por compressão direta. A sobrevivência percentual dos esporos de Bacillus subtilis diminuiu com o aumento da concentração do agregante. O estudo mostrou que a goma de Albizia é capaz de conferir maior plasticidade aos materiais e apresentou maior redução da contaminação microbiana nas formulações. O método de compressão direta produziu comprimidos com viabilidade reduzida de contaminantes microbianos.